Spiritual Transcendence in Psychotherapy: A Relational, Pragmatic, and Semiotic Approach - Salimi, Barbod (Open theology, 2016)
The last several decades have ushered in an abundance of creative activity and wisdom with regard to spiritually and/or religiously informed psychotherapy. Most of these pursuits have led to significant and positive changes, both in thought and practice, in the way that human psychology is seen as intersecting (and interacting) with religious, theological, and spiritual dimensions of experience. At the same time much has been neglected amidst these advances. In the present paper, we submit that one vital area of neglect may be found in an implicit retreat from sacred encounter in favor of instrumentalized approaches to psychotherapy. We argue for a spiritually transcendent psychotherapy that implicitly attends to relational and semiotic phenomenology while retaining pragmatic gain.